AN ANALYSIS OF INTERPERSONAL METAFUNCTION IN “A HEAD FULL OF DREAMS” COLDPLAY’S ALBUM OF SONG LYRICS - Hendri Pranoto; Dwi Setiyadi; Yuli Kuswardani (Universitas 17 Agustus 1945 Semarang, 2020)
Coldplay is a band from the British, begin their career in 1998. Until today Coldplay have already eight songs album, one of the albums is A Head Full of Dreams. In its album, the songs make use of interpersonal metafunction. The objectives of the research to describe the mood types used in the lyrics of Coldplay’s album A Head Full of Dreams, to describe the modality in the lyrics of Coldplay’s album A Head Full of Dreams. The researcher uses descriptive qualitative for the research approach and content analysis for the type of research. The data is this research is taken from A Head Full of Dreams’ song lyrics which are taken by Coldplay’s official website. Documentation is used in the data collecting technique. The researcher uses the data analysis technique Flow model by Miles and Huberman and functional approach. The result of the research reveal: (1) mood shows three kinds of mood which are declarative, imperative, and interrogative and found 76 declarative, 83 imperatives, and 2 interrogatives. (2) Modality shows there are categorized of modality, which is low, medium, and high and found can’t, can, will, would, and might. Keywords: Interpersonal metafunction, Coldplay’s album song lyrics, A Head Full of Dreams